Current situation, causes, and countermeasures to NIP vaccine shortages in Guangzhou, China - Zhiqun Li; Jindong Xu; Jianxiong Xu; Huifeng Tan; Chunhuan Zhang (Taylor & Francis Group, 2020)
From 2017 to 2018, Guangzhou experienced a shortage in 3-6 types of National Immunization Program (NIP) vaccines. To evaluate the current situation and causes of the NIP vaccine shortage, we analysed the duration, intensity and causes of the shortage from data in the vaccine information system of the Guangzhou Center for Disease Control and Prevention; we also proposed countermeasures to resolve the shortage. In 2017, there were shortages of three types of NIP vaccines in Guangzhou. The most affected vaccines were inactivated poliovirus (IPV) vaccine and meningococcal group AC (MenAC) vaccine, accounting for 39.5% and 16.5% of the reported shortages, respectively. In 2018, the shortage extended to six vaccine types; the most affected were diphtheria, tetanus and pertussis (DTP) vaccine, MenAC vaccine, and Bacille Calmette Guerin (BCG) vaccine. The four main causes for the shortage were: 1) an insufficient production capacity; 2) a delay in batch issuance; 3) vaccine-related events; and 4) an extended bidding procurement cycle. Four solutions are proposed: 1) expand production output; 2) exempt creditworthy enterprises from batch inspections; 3) establish alternative enterprises and emergency use authorizations; and 4) establish public health funds and stockpile storage systems.